(untitled) (Bangladesh Journal of Child Health, 2012)
Febrile seizures (FS) are the most common convulsive event in children. This condition has been described since the time of Hippocrates. The etiology of the febrile seizures are still unclear. In FS, there is a strong familial predisposition. This does not exclude infections as a causative factor because subtle genetic polymorphisms have been demonstrated to affect the course of infections. In an earlier review of the world literature (1924-1964), except for roseola infantum, viral infections as a cause of febrile seizures were rarely diagnosed. Reports of viral infections in the etiology of febrile seizures have increased in number in the past decade. In the first half of the twentieth century, infections identified with febrile seizures were mainly upper respiratory in type and the etiologic agent was unknown or bacterial. We review i) the role of infection viral and bacterial; ii) the role of genetic and environmental factors; iii) the role of electrolyte and metabolic factors; and iv) the role of cytokines. With the help of new diagnostic tools such as PCR, the viral agents are detected in CSF far more often than previously thought, even in the absence of pleocytosis of the CSF. This makes it difficult to distinguish FS from acute encephalitis. FS may be caused by neuroinvasion or intracerebral activation of viruses. By reviewing etiology and risk factors of FS we can identify the points to be focused in therapeutic interventions and trials and also the fields of future studies will be explored. DOI: http://dx.doi.org/10.3329/bjch.v34i3.10361 BJCH 2010; 34(3): 103-112